Case Report: A Malignant Liver and Thoracic Solitary Fibrous Tumor: A 10-Year Journey From the Brain to the Liver and the Spine - Mao, Min; Zhou, Lei; Huang, Chaojun; Yan, Xudong; Hu, Shuo; Yin, Huabin; Zhao, Qinghua; Song, Dianwen (Frontiers in Surgery, 2020)
Solitary fibrous tumours are rare neoplasms that originate from mesenchymal tissues and have been found to occur in any site, including the spine and liver. Although most Solitary fibrous tumours have benign features, 10-20% of these tumours are malignant and prone to metastasis. No previous reports have described a malignant and metastatic Solitary fibrous tumour arising in both of the liver and thoracic vertebrae. In this article, we present the case of a 60-year-old woman who underwent gross total resection of a meningeal tumour in 2007. She presented 10 years later with a thoracic vertebral mass that caused relentless pain and a lesion in the right lobe of liver. She underwent marginal excision of the T3 tumour with T2-4 pedicular screw fixation in March 2017, and then a right hemi-hepatectomy was performed to remove the liver lesion by gross total resection in June 2017. Both of the lesions were confirmed to be a metastatic tumour after surgery.